Do Family Values Shape the Pace to Return to Work after Childbirth? - Mireia Borrell-Porta (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper argues that the pace to return to work after childbirth is not independent of family values. I evaluate the effect of a parental leave policy reform in Germany in 2007-aimed at incentivizing an earlier return to work - on the return to work of mothers who hold different family values. Using a regression discontinuity design and an epidemiological approach to family values I find that although the policy has substantially increased the pace to return to work of mothers regardless of their family values, mothers upholding traditional family values keep returning to work at a slower pace than mothers with liberal family values.
Keywords: J13; J21; J22; Z10; 330; parental leave; family values; female labour supply; epidemiological approach